PENGARUH HAMBATAN SAMPING TERHADAP KAPASITAS JALAN DAN KECEPATAN LALU LINTAS - STUDI KASUS JL. PANGERAN DIPONEGORO - Baderan, Ramdhan; Abdullah, Aning Yustica Sari; Tome, Nurhediyati (Jurnal Teknik Sipil, Arsitek, Perencanaan Wilayah (J-TSIAP), 2024)
This research was conducted on Jalan Pangeran Diponegoro, Limba B Village, South Kota District. The aim of this research is to determine the effect of side obstacles on the characteristics of traffic flow on Jalan Pangeran Diponegoro, Limba B Village, South Kota District. Based on vehicle data, the maximum traffic volume occurred on Monday at 15.00 – 16.00 WITA, 508.5 pcu/hour, and capacity was 1996,198 pcu/hour. This shows that the capacity is still greater than the maximum traffic volume that occurs. Based on the calculation results of the capacity value (C = 1996,198 pcu/hour) the ability to accommodate the flow or volume of traffic on the Jl. Prince Diponegoro is still included in category C, where the flow conditions are stable, the traffic speed is approximately greater or less than 65 km/hour, the traffic volume is around 50% of capacity (1400 pcu/hour/lane). Traffic conditions, factors which include side obstructions from the road, including the number of vehicles waiting for passengers to stop on the road, and the presence of vehicles standing or parking on the shoulder of the road which can cause congestion.